Characteristics and driving factors of the technology cooperation network evolution: a case study of solid waste treatment field in China. Issue 5 (4th May 2023) - Ma, Yonghong; Yang, Xiaomeng; Qu, Sen; Kong, Lingkai
ABSTRACT: The construction and development of technology cooperation network are very important to improve the efficiency of technology R&D. Based on the cooperative patent data in the field of solid waste treatment in China, this paper analyses the structural, spatial and organisational characteristics of the technology cooperation network evolution by using the social network analysis (SNA) method. Meanwhile, the exponential random graph model (ERGM) is used to explore the driving factors of the network evolution. The present results show that the network tends to form a convergent structure and transitive structure, while the intermediary structure is not conducive to the formation of the network. The R&D capability of the entity has no obvious impact on the network evolution, but the positive impact of degree centrality is significant. The negative influence of the structural holes gradually appears in the late stage of network evolution. The geographical homophily has a long-lasting and significant positive effect on network evolution. However, the effect of organisational homophily on the network evolution gradually weakens over time. This study expands the research perspective of technology cooperation network and provides a practical reference for promoting technical cooperation in the field of solid waste treatment.